Shear velocity and intrinsic attenuation variation within the Aegean Lithosphere deduced from surface waves - Kassaras, I.; F. Louis; Makropoulos, K.; A. Magganas (31st General Assembly of the European Seismological Commission, 2008)
This paper presents a new shear velocity and attenuation model for the lower crust and litho- sphere of the Aegean region, obtained by inversion of broadband surface-wave phase veloci- ties and attenuation coefficients. We have two main motivations for conducting this study. First, knowledge of the regional structure of the Aegean lithosphere is fundamental for understanding the tectonic framework and mantle dynamics, posing constraints on possible models of deformation and evolution. Second, the exponential dependence of Q with temperature implies that attenuation tomography could explain better hot regions (high attenuation) than elastic tomography. Furthermore, elastic velocity is highly influenced by the constitution of the medium. In case of strong lateral Q variations, elastic parameters also vary. Hence, it is important to combine results of elastic and anelastic tomography. Apparently, the high rates of deformation in the Aegean constitute this region particularly interesting in this perspective.